Development of a socially assistive human-robot interface for cardiac rehabilitation (2019)
According to the world health organization, cardiovascular diseases (CVD’s) are a major cause of death worldwide, taking the lives of 17.9 million people every year. Cardiac Rehabilitation (CR) programs are dedicated to approaching this problem and reduce mortality due to the presence of a second event. However, the main problem regarding these programs is associated with low adherence and attendance to the therapies, causing a major public health issue that generates high health care expenditures. In this context, different approaches have been considered to motivate people to attend the therapies and continue with the treatment. Socially Assistive Robotics (SAR) has been gaining significant attention in multiple health care applications by providing assistance through social interaction rather than physical interaction. Social robots have provided support, motivation, and monitoring in areas such as stroke rehabilitation, patients with dementia, physical rehabilitation, and autism. These interventions have reported promising results, showing that patients feel more engaged and motivated to continue the therapeutic treatments. These findings are encouraging to explore the effect of SAR in CR. This master thesis presents the development and validation of a socially assistive human-robot interface for CR. This interface integrates a Human-Computer interface (HCi) designed to perceive the environment and allow the interaction with the user and the therapy context. In conjunction with the HCi, the system integrates a social robotic platform, which is programmed to socially interact with the user, providing monitoring and motivation, according to the information generated by the HCi. In order to evaluate the effect that the SAR system produces in CR patients, this thesis conducted a series of experimental studies. First, a longitudinal study was carried out with a group of six patients divided into 2 groups (control and intervention) aiming to compare the effect of the robot-therapy against conventional therapy. Furthermore, an acceptance and perception study was conducted for a group of 28 patients and 15 clinicians to evaluate their opinions, experience, and expectations with the system. Results demonstrate significant potential in the incorporation of social robotic companions in CR, where patients that interacted with the robot showed improvement of their physiological condition (i.e., reduction of resting hearth rate and increasing of the recovery capability after exercise) compared to the baseline. Moreover, patients that interacted with the robot felt motivated and encouraged to continue the treatment, and clinicians perceive the system as a useful tool to support their tasks and provide better assistance. Demonstrating that SAR holds promising potential to be a feasible approach that enhances CR effects and help to improve the quality of life of cardiac patients.